Fiscal Federalism and Economic Welfare in Nigeria: an Econometric Analysis. - Eshenake, S.J.; Oyovwi, O. Dickson (European Journal of Sustainable Development, 2013)
The objective of this paper is to investigate the effects of fiscal federalism oneconomic welfare in Nigeria between 1970 and 2009 using an econometricapproach. The ordinary least square (OLS) technique is adopted. The AugmentedDickey-Fuller test was used to test for unit root and it was discovered that all thevariables are I (I) except Fiscal Autonomy Ratio (FAR) that is I (O). Also theJohasen co-integration test was used to test for the long term properties of thevariables and the result shows that there exist a long-run relationship betweenmeasures of FD and PCI. The short-run dynamic result shows that measuresfiscal decentralization have mixed relationship with Per capita income with R2 of0.907 and F-statistic of 30.26. The dummy variable shows that there is asignificant difference between civilian and military regimes with respect to fiscaldecentralization and economic welfare in Nigeria during the period of study. Thestudy recommends among others that the National Revenue mobilization,Allocation and Fiscal Commission (NRMAFC) should be independent and beallowed to meaningfully undertake its functions regarding fiscal relationshipbetween the various levels of government.